2023
DOI: 10.1007/s40429-023-00476-5
|View full text |Cite
|
Sign up to set email alerts
|

Kratom’s Emergence and Persistence Within the US Polydrug Epidemic

Abstract: Purpose of Review Use of “kratom” products, derived from the bioactive botanical Mitragyna speciosa have increased amidst US polydrug use epidemics. Kratom alkaloids interact with opioid, serotonergic, adrenergic, and other receptors and regular users have described experiencing a wide range of effects. Some with polydrug use histories have reported using kratom as a substitute for other drugs or to nonmedically self-manage substance use disorder (SUD) symptoms. Data des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…These findings are aligned with prior surveys that evaluated the consumption patterns of kratom. 22,23 Our survey also explored participants' history with adverse effects that could reasonably be related to their kratom consumption, with the most frequently reported adverse effects being withdrawal and tolerance (Supplement Table 2, http://links.lww.com/JAM/ A491). One of the caveats in diagnosing a SUD is that tolerance and withdrawal can occur in appropriate therapeutic doses and for medical use of prescribed medications.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are aligned with prior surveys that evaluated the consumption patterns of kratom. 22,23 Our survey also explored participants' history with adverse effects that could reasonably be related to their kratom consumption, with the most frequently reported adverse effects being withdrawal and tolerance (Supplement Table 2, http://links.lww.com/JAM/ A491). One of the caveats in diagnosing a SUD is that tolerance and withdrawal can occur in appropriate therapeutic doses and for medical use of prescribed medications.…”
Section: Discussionmentioning
confidence: 99%
“…The current review also indicates that researchers in the kratom field continue to conflate kratom alkaloids, such as mitragynine, kratom products derived from dried and processed leaf material, and fresh leaf preparations without considering potential health and safety implications related to the overall differences in chemical content or potency of these different types of kratom products [4]. Currently, there is a paucity of published research, investigating potential effects of different plant cultivation methods, methods of processing of plant material, and manufacturing processes and standards utilized in production of consumed products.…”
Section: Discussionmentioning
confidence: 99%
“…Historical claims of medicinal or pharmacological effects of chewing fresh leaves of kratom tree (Mitragyna speciosa) native to Southeast Asia [1][2][3], supplemented by narrative accounts of potential health benefits of products derived from kratom and consumed in the United States and other countries in the West [4] garnered an increasing interest among researchers, clinicians, and the public in recent years. Although there is a growing demand for kratom-derived products among the United States consumers, there is also a paucity of rigorously collected scientific data on human pharmacological safety profile of kratom phytochemicals and very limited scientific data on their dose-related effects in humans [5].…”
Section: Introductionmentioning
confidence: 99%
“…Complexities of kratom use confound interpretation of use-related risk or adverse events. One example is that kratom persists as a harm-reduction method to reduce opioid and other substance use ( 8 , 9 ). Previously, some consumers with opioid use disorder (OUD) history reported that kratom is not preferred over illicit opioids and do not report using kratom to achieve a euphoric “high” ( 10 , 11 ).…”
Section: Context Of Kratom Usementioning
confidence: 99%